Pelatihan dan Pendampingan Guru Mengaji di Kecamatan Sinjai Utara - Idris, Mukrimah; Fajaruddin, Fajaruddin; Noerhaq, Muh; Alfajri, Alfajri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The number of Qur’anic teachers (Guru Mengaji) in North Sinjai District has increased significantly each year. However, a major challenge remains in their classroom management skills, as well as the teaching methods used, which are still largely monotonous. Many Qur’anic educational institutions continue to rely on traditional methods, highlighting the need for innovation to improve instructional quality. Therefore, training and mentoring programs were conducted for Qur’anic teachers at the district level in North Sinjai to enhance their competencies in teaching the Qur’an and Islamic values to students (santri). To address these issues, the program employed training and mentoring approaches in collaboration with DPK BKPRMI of North Sinjai District. The results of the program show that 80% of Qur’anic teachers demonstrated an understanding of the materials and were ready to apply them in real teaching practices. Meanwhile, 50% of the participants were able to directly practice classroom management, implement learning methods, and apply evaluation techniques through microteaching activities. In addition, the program led to the formation of a Qur’anic Teachers Community Group in North Sinjai District, which facilitates communication and information sharing among teachers.